A case report of delusional parasitosis by proxy: a rare entity - Caroline Chivily; Brianna Glover (BMC Psychiatry)
Abstract Background Delusional parasitosis is a rare, fixed, false belief that an individual is infested with parasites or other living organisms despite no laboratory evidence to confirm this belief. It can manifest as a shared belief, folie à deux, or by proxy. Case presentation This case report describes an 8-year-old patient with Trisomy 21 with delusional parasitosis by proxy. The patient’s mother remained fixated on the patient having a parasitic infection despite extensive reassuring evaluations. There were multiple normal-appearing pictures and videos of the patient’s urine, stool, skin and throat shown to the medical team, consistent with the “specimen sign” described in the literature. Conclusions Delusional parasitosis is rare and can be difficult to diagnose and treat. It has even more complexity and implications in pediatric or other vulnerable populations. A multidisciplinary treatment approach is important to build trust and prevent harm.